Risky alcohol use and age at onset of regular alcohol consumption in relation to frontal lobe indices, reward sensitivity, and rash impulsiveness - Lyvers, M.; Duff, Helen; Hasking, Penelope (Routledge, 2011)
Excessive alcohol consumption has been linked to predisposing traits that may reflect frontal lobe functioning, an idea explored by this study. The study recruited 132 adults of both genders aged 18-68 years who completed an online questionnaire battery. Sensitivity to punishment was the primary variable associated with age of onset for weekly drinking. The relationship between disinhibition and drinking behavior, as assessed by the AUDIT, was partially mediated by sensitivity to reward. The findings of this study suggest that several interrelated and heritable personality and neurobehavioral traits may promote earlier as well as riskier alcohol consumption.